Exergy analysis of a diesel engine fuelled with Aegle marmelos de‐oiled seed cake pyrolysis oil opus. Issue 5 (1st May 2020) - Baranitharan, P.
Abstract: Biofuel is a renewable fuel and can be used as a replacement for diesel. Pyrolysis oil can be derived from non‐edible de‐oiled seed cakes. This investigation focuses on the exergy investigation of a compression ignition (CI) engine to maximize the work exergy (availability) and minimize the destroyed exergy, powered by Aegle marmelos (AM) de‐oiled seed cake bio‐oil blends. A dual blend of diesel and AM pyrolysis oil was taken in ratios, F0 = 100 + 0, F5 = 95 + 5, F10 = 90 + 10, F15 = 85 + 15, and F20 = 80 + 20 and were tested on a constant speed CI engine at standard compression ratio. The investigational analysis exhibited that a high amount of oxygen content in AM pyrolysis oil blends increased the brake thermal efficiency and decreased the brake‐specific fuel consumption compared with diesel (F0). The owing exergy efficiency was obtained from the F20 blend (57.21%) at 100% load (W). Based on the investigation, considering availability and performance behavior of F5, F10, F15, and F20 blends were suggested as suitable biofuel alternatives to diesel.